Developing and validation of religious education curriculum in preschool - Zeinab Ashrafi Soltan-Ahmadi; Sadegh Maleki Avarsin; Javad Keyhan; jahangir yari (مدیریت و چشم انداز آموزش)
AbstractThe purpose of this research is to compile and validate the curriculum of religious education in the preschool period. The research method is applicable in terms of purpose, mixed (qualitative-quantitative) in terms of the type of data, and is a sequential exploratory combined approach. The statistical population in the qualitative section includes 16 curriculum studies experts, Islamic education experts, and instructors of this course; and in the quantitative section, it includes 200 preschool children. Sampling was done purposefully and according to the theoretical saturation of the data. The tools of data collection are semi-structured interviews and questionnaires. Theme analysis was used to collect information in the qualitative stage, and structural equation modeling in the quantitative stage. The data obtained from the interviews were analyzed using Nvivo version 8 software in the form of thematic analysis-based, inductively on the "theme network" technique, and during the stages of coding (open, central and selected), and the proposed model of religious education for preschool children was compiled and its assumptions were used to prepare a survey questionnaire in the quantitative stage and evaluate its validity. To ensure the validity of the instrument, expert consensus was used using Delphi method and Cronbach's alpha method was used to determine reliability (α = 0.83). The data were collected with convergent validity (AVE > 0.5) and composite reliability (CR > 0.7), and were analyzed by PLS software to validate the model from structural equation modeling using partial least squares. The results showed that the identified characteristics can predict religious education curriculum components in a favorable way (R2=0.552). Finally, the fit of the overall research model was confirmed (GOF=0.438).Extended abstractIntroductionEducation is the most important and basic aspect of human life. In addition to the role and function of the family as an effective and important factor in children's issues and problems (Abbass Ghorbani & Naghdi, 2020), today the role of educational systems, especially education, is not limited only in learning science, developing skills, cognitive abilities, and preparing children and teenagers to entering higher education degrees, but its cultural and educational function is very important in the progress and development of societies (Nasiri et al, 2022). Considering the role of education and the duties of the school in achieving religious goals and responding to the needs of society, religious education has been considered as the most important goal in the current educational and official systems (Vaghari Zamharir et al, 2017). Religious education or divine education is the most important part of Islamic education and the philosophy of the mission of the prophets, and the most basic duty of the divine parents and guardians and educators of the Islamic human society. Religious education, so to speak, is an aspect of the educational process that oversees the development of cognitive, emotional, and practical (experiential) dimensions in terms of commitment to religious standards; in other words, religious education is the development and strengthening of religious beliefs, religious moods and emotions, and adherence to rituals, and it considers religious customs to realize a civilized personality (Keyhan, 2021). In the current research, an attempt is made to answer the question: what is the design of the religious education curriculum model at the preschool level in Iran's education?Theoretical frameworkDesired Religious education has always been one of the main concerns of education systems. Religious education or divine education is the most important part of Islamic education and the philosophy of the mission of prophets and the most basic duty of divine guardians and guardians and educators of Islamic human society (Ashrafi Soltan-Ahmadi et al, 2021). Religious education is to provide natural and introspective opportunities for people to discover the sublime brilliance of religion through personal experience and inspiration from their nature (Sharifi Darvaze et al, 2021). In another definition, religious education considers the growth and strengthening of religious beliefs, religious moods and emotions, and adherence to religious rites and customs to realize a civilized personality (Kiyomarthi, 2013).Samadi (2022) in his research on the causes of the vulnerability of the educational system in developing students' religious identity, came to the conclusion that the policy weakness of the educational system in the training of human resources, religious education curriculum, and lack of attention to developmental requirements of students and poor performance of religious institutions, media and peer groups are among the vulnerability factors in developing religious identity.Zare et al, (2022) investigated the analysis of religious education in students. The results indicated that special attention should be paid to the exemplary role of the teacher, scientific and religious competence, acceptability and popularity of the teacher for the students, and they also emphasized on expressing religious issues in a simple and understandable way and in the form of specific behaviors and using various educational tools such as books as well as holding attractive ceremonies and competitions.Research methodologyThe research method is applicable in terms of purpose, mixed (qualitative-quantitative) in terms of the type of data, and is a sequential exploratory combined approach. The statistical population in the qualitative section includes 16 curriculum studies experts, Islamic education experts, and instructors of this course; and in the quantitative section, it includes 200 preschool children. Sampling was done purposefully and according to the theoretical saturation of the data. The tools of data collection are semi-structured interviews and questionnaires. Theme analysis was used to collect information in the qualitative stage, and structural equation modeling in the quantitative stage.Research findingsThe data obtained from the interviews were analyzed using Nvivo version 8 software in the form of thematic analysis-based, inductively on the "theme network" technique, and during the stages of coding (open, central and selected), and the proposed model of religious education for preschool children was compiled and its assumptions were used to prepare a survey questionnaire in the quantitative stage and evaluate its validity. To ensure the validity of the instrument, expert consensus was used using Delphi method and Cronbach's alpha method was used to determine reliability (α = 0.83). The data were collected with convergent validity (AVE > 0.5) and composite reliability (CR > 0.7), and were analyzed by PLS software to validate the model from structural equation modeling using partial least squares. The results showed that the identified characteristics can predict religious education curriculum components in a favorable way (R2=0.552). Finally, the fit of the overall research model was confirmed (GOF=0.438).ConclusionThe present research was conducted with the aim of compiling and validating the religious education curriculum in the preschool period. The results of this research is aligned with the results of Aghili et al, (2019), Naderi et al, (2019), Rahayu & Munadi (2019), Mansoorian (2022), Shamshiri & Nowzari (2018), Placklé et al, (2014), Maleki (2013), and Mikailo & Sultan Al-Goraei (2015). Mansoorian (2022) has emphasized in his research that by using the problem solving method, students' understanding and perception can be brought to the level of abstract perception. It means that they should not consider what they learn as reserved; but they understand and touch those contents with all their being. Shamshiri & Nowzari (2018) in presenting the local model of religious education for preschool children emphasized and necessitated the method of grounding by providing practical learning activities for the active participation of children in the process of religious education.